*WILL MARK YOU BRAINLIEST!!!!!*

Answer:
[tex]x=12[/tex]
Step-by-step explanation:
[tex]\frac{\sqrt{3x} }{\sqrt{x-8} } =3[/tex]
[tex]\sqrt{3x}=3\sqrt{x-8}[/tex]
[tex]\left(\sqrt{3x}\right)^2=\left(3\sqrt{x-8}\right)^2[/tex]
[tex]3x=9x-72[/tex]
[tex]3x-9x=-72[/tex]
[tex]-6x=-72[/tex]
[tex]x=12[/tex]
Answer:
[tex] \frac{ \sqrt{3x} }{ \sqrt{x - 8} } = 3[/tex]
[tex] \sqrt{3x} = 3 \sqrt{x - 8} [/tex]
[tex]3x = (3 \sqrt{x - 8} )^{2} [/tex]
[tex]3x = 9(x - 8)[/tex]
[tex]3x = 9x - 72[/tex]
3x - 9x = -72
-6x = -72
x = 12